Global Perspectives on Recognising Non-formal and Informal Learning: Why Recognition Matters - Singh, Madhu (Cham Springer Nature, 2015)
Professional & Vocational Education; Lifelong Learning/Adult Education; Educational Policy and Politics; Assessment, Testing and Evaluation
English
Keywords: Education; Coins, banknotes, medals, seals (numismatics); Professional & Vocational Education; Lifelong Learning/Adult Education; Educational Policy and Politics; Assessment, Testing and Evaluation